Pengaruh Trust dan Loyalty Terhadap Brand Equity dalam Meningkatkan Repurchase Intention pada Retail - Yulis Fitria; Anak Agung Ketut Diatmika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In an increasingly competitive business world, retaining loyal customers is more cost- effective and has the potential to generate higher revenues than attracting new customers, with trust and innovation playing a key role in strengthening brand equity and increasing loyalty and repurchase intention. Therefore, companies need to integrate innovative and trust-building strategies to ensure customer loyalty and long-term success in an ever- changing market. The aim of this research is to identify factors that influence consumer loyalty to certain brand equity and products, as well as to understand the mechanisms underlying consumer intention to repurchase. This research was conducted in Jabodetabek with a causality descriptive research design with a quantitative method approach and using simple random sampling techniques. Data was collected from 140 respondents who live in Jabodetabek who have shopped at Superindo at least twice in the last 2 months. The conceptual model was analyzed using Structural Equation Modeling. Research findings reveal that loyalty has no influence on the brand equity. Then, trust is positively related to loyalty and brand equity. Furthermore, brand equity is positively related to repurchase intention. The contribution of this research can increase customer trust, loyalty and repurchase intentions, which will ultimately strengthen Superindo's position in the market and encourage long-term growth.